Independent Auditor’s Report: Messages Conveyed and Implications - Saher Aqel (Acta Universitatis Danubius: Oeconomica, 2014)
Auditing plays a crucial role in the business environment by providing assurance services to the public so as to decrease information risk by increasing the reliability of financial information provided by the business entities. As the final product of the audit, the audit report is a way by which the auditor communicates with the public the findings of the audit process. The auditor‟s report is the only aspect of the work of auditor that can be available to the public. Thus, users are likely to assess the auditor‟s professionalism and competence by this report. The purpose of this study is to address the meaning and implication of the audit report in addition to a discussion of the messages perceived from the auditor‟s report. Differences in perceptions of the meaning of the auditor‟s report may exist between the auditors and users. Users may misperceive the nature and scope of the audit function and the level of assurance when they read the audit report